Validation of an interview-only version of the Dimensional Yale-Brown Obsessive-Compulsive Scale (DY-BOCS) in treatment-seeking youth with obsessive-compulsive disorder. (January 2019) - Cervin, Matti; Perrin, Sean; Olsson, Elin; Claesdotter-Knutsson, Emma; Lindvall, Magnus
Highlights: Obsessive-compulsive disorder is a highly heterogeneous disorder. The DY-BOCS is the most comprehensive measure of OCD heterogeneity. An interview-only version of the DY-BOCS showed intact psychometric properties. This version can be carried out by a clinician in one hour or less. The measure was sensitive to the effects of treatment for pediatric OCD. Abstract: There is a growing body of evidence suggesting that individuals with obsessive-compulsive disorder (OCD) may be sub-typed along different symptom dimensions. These dimensions may help explain responsiveness to current treatments. The Dimensional Yale-Brown Obsessive-Compulsive Scale (DY-BOCS) is a validated instrument involving a self-report screening tool followed by a structured interview in which the presence/absence and severity of OCD symptom dimensions are assessed and rated. The present study investigated the validity of a briefer, interview-only version of the DY-BOCS modified for use in routine care. Clinically-referred children and adolescents ( N  = 119) with OCD were administered the DY-BOCS along with other measures of OCD, anxiety, depression, and overall functioning and a subset ( N  = 100) were reassessed on average 14 months after initial assessment. This briefer, interview-only version of the DY-BOCS demonstrated high levels of internal consistency and correlated in the moderate to strong range with alternative measures of OCD severity and OCD symptom dimensions. Change scores on the DY-BOCS from baseline to follow-up were significantly correlated with change scores on the alternative measures of OCD and clinician-rated improvement, suggesting that this brief version of the DY-BOCS is valid and sensitive to the effects of treatment for OCD delivered in routine clinical care.